KOMUNIKASI IDEOLOGI BAND INDIE MELALUI DESAIN COVER ALBUM STUDI KASUS: THE S.I.G.I.T. - Yosua Reydo Respati (Jurnal Dimensi DKV Seni Rupa dan Desain, 2016)
AbstractIndie Band Comunication Ideology through Album Cover Design Study Case: The S.I.G.I.T. Album cover as a part of music records has an important role as a visual communication strategy. Besides being a medium to persuade the audience, album cover able to deliver messages related to musical vision, idealism and ideology of a band.Major label choose to produce profit-oriented bands, while indie bands use album cover as a visual communication about their idealism. This research specifically discuss the visual appearance of the indie band The S.I.G.I.T.’s album cover design as a study case. Through semiotics methods this research analyzed the sign structure and significance of album cover design by The S.I.G.I.T. The analysis is conducted by describing the signelements and interpretation of the sign as a unity (supersign). Based on the analysis, will be the interpretation of the ideological significance and the idealism that make up the image of the band that communicated to the audience. This research can beuseful for the subculture research development of album cover design with approach of creative visual communication strategy.AbstrakKomunikasi Ideologi Band Indie melalui Desain Cover Album Studi Kasus: TheS.I.G.I.T. Cover album sebagai bagian dari album rekaman memiliki peran pentingdalam strategi komunikasi visual. Selain menjadi media promosi yang mempersuasiaudiens, cover album menyampaikan pesan yang merangkum visi bermusik, idealismedan ideologi sebuah band. Berbeda dengan band major label yang berorientasi padasisi komersil dan popularitas, band indie menggunakan cover album sebagai mediakomunikasi akan eksistensi idealisme mereka. Penelitian ini secara spesifik membahasdesain cover album band indie The S.I.G.I.T. sebagai studi kasus. Melalui metodesemiotika dilakukan analisa terhadap struktur tanda dan tingkatan makna tanda padadesain cover album The S.I.G.I.T. Analisa dilakukan dengan menjabarkan elemen tandadan dinterpretasi sebagai kesatuan tanda (supersign). Berdasarkan analisa tersebutdilakukan kajian terhadap muatan ideologi yang membentuk image/citra band yangdikomunikasikan ke audiens. Penelitian ini dapat bermanfaat bagi kajian produkbudaya subkultur dan pengembangan desain cover album dengan pendekatan strategikomunikasi visual yang kreatif.Kata kunci: desain cover album, band indie, ideologi, semiotika